2009
DOI: 10.48550/arxiv.0911.5402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hom-quantum groups III: Representations and module Hom-algebras

Donald Yau

Abstract: We study Hom-quantum groups, their representations, and module Hom-algebras. Two Twisting Principles for Hom-type algebras are formulated, and construction results are proved following these Twisting Principles. Examples include Hom-quantum n-spaces, Hom-quantum enveloping algebras of Kac-Moody algebras, Hom-Verma modules, and Hom-type analogs of Uq(sl 2 )module-algebra structures on the quantum planes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…We also show that comodule Hom-coalgebras can be deformed from comodule coalgebras via endomorphisms. All of our results are dual to D. Yau's work in [13,15]. The difference between our's and his is that, since we are dealing with comodules and coalgebras, we will find that the Sweedler notions [10,2] are more convenient for us to do the work.…”
Section: Introduction and Main Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…We also show that comodule Hom-coalgebras can be deformed from comodule coalgebras via endomorphisms. All of our results are dual to D. Yau's work in [13,15]. The difference between our's and his is that, since we are dealing with comodules and coalgebras, we will find that the Sweedler notions [10,2] are more convenient for us to do the work.…”
Section: Introduction and Main Resultsmentioning
confidence: 66%
“…The universal Hom-associative algebra of a Hom-Lie algebra was studied in [11]. Module Hom-algebras and Comodule Hom-algebras have been studied by D. Yau in [13,14,15]. Some other Hom-type algebras such as n-ary Hom-Nambu algebras and n-ary Hom-Nambu-Lie algebras have been studied in [1,16].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…The generalized notions, Hom-bialgebras, Hom-Hopf algebras were developed in [3], [5], [6]. Further research on various Hom-Lie structures and Hom-type algebras by many schlors could be found in [7], [9], [16], [17]. Quasitriangular Hom-bialgebras were considered by Yau ([8], [9]), which provided a solution of the quantum Hom-Yang-Baxter euqation, a twisted version of the quantum Yang-Baxter equation ( [10], [11]).…”
Section: Introductionmentioning
confidence: 99%
“…Yetter-Drinfeld modules over Hom-bialgebras and their category have been studied in [36]. For further results about generalizations of quantum groups and related structures see [8,43,44,45]. In [18], Hom-quasi-bialgebras have been introduced and concepts like gauge transformation and Drinfeld twist generalized.…”
Section: Introductionmentioning
confidence: 99%